The Criminal Prosecution for the Crime of Electronic threat According to Jordanian Legislation - aleshoush, Mahmoud Aref (Journal of Ecohumanism, 2024)
This study addresses an important and emerging topic, which is electronic threat crimes and their criminal consequences according to the new Jordanian Cybercrime Law of 2023. The study is divided into two sections. The first section discusses the legal nature of electronic threat crimes, divided into two parts: the nature of electronic threat crimes and the elements of electronic threat crimes. The second section discusses the mechanism of combating electronic threat crimes, also divided into two parts: how to prove electronic threat crimes and the penalty for threat crimes using electronic means. The study concludes with important findings that highlight the need for specialized teams to investigate electronic threat crimes and adapt to modern developments in dealing with intelligent criminals who possess different characteristics from traditional criminals. The conclusion also includes recommendations to establish units within security institutions to handle electronic threat crimes, receive threat reports, and develop high-level skills to track such intelligent criminals.